ORDEN I KLASSIFIKATIONEN: Om repræsentationen og udbredelsen af religiøs viden - Højbjerg, Christian Kordt (Tidsskriftet Antropologi, 1997)
Christian Kordt Højbjerg: The Order of Classification. On the Representation and Distribution of Religions Knowledge The purpose of the article is to present and discuss the apparent contradiction between differentiated cognition and cultural consensus with regard to the religious category sale among the Loma people in Guinea and Liberia. Opposing traditional classificatory approaches to cultural knowledge in anthropology, it is argued that the complex religious category is more adequately rendered through a cognitive and distributive approach. The first part of the article identifies three different, although frequently coexisting mechanisms of distribution and acquisition of sale knowledge, which are labeled respectively continuous (semantic memory), discontinuous (episodic memory), and esoteric (secret knowledge acquisition). In the second part, an analysis of a sacrificial ritual leads to the conclusion that the sale category is an awkward classificatory case, which helps to build cognitive bridges between separate domains of reality. This general cognitive quality of the sale category serves to apprehend sale as a collectively shared representation, irrespective of its multi-vocality and differentiated cognition.